2022
DOI: 10.1186/s12879-021-07012-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of presepsin and procalcitonin in non-infectious organ failure, sepsis, and septic shock: a prospective observational study according to the Sepsis-3 definitions

Abstract: Background We investigated the diagnostic and prognostic value of presepsin among patients with organ failure, including sepsis, in accordance with the Third International Consensus Definitions for Sepsis and Septic Shock (Sepsis-3). Methods This prospective observational study included 420 patients divided into three groups: non-infectious organ failure (n = 142), sepsis (n = 141), and septic shock (n = 137). Optimal cut-off values of presepsin to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 34 publications
(52 reference statements)
0
35
0
8
Order By: Relevance
“…It can be used as a supplementary factor for stratifying sepsis patients with different prognosis groups [ 26 ]. In addition, presepsin is effective in distinguishing between infected and noninfectious organ failure and helps clinicians determine patient prognosis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can be used as a supplementary factor for stratifying sepsis patients with different prognosis groups [ 26 ]. In addition, presepsin is effective in distinguishing between infected and noninfectious organ failure and helps clinicians determine patient prognosis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of presepsin for diagnosing sepsis (including shock) using a cut-off value of 508 pg/ml were 87%, 86%, 93%, 76%, and 87%, respectively. A recently published study by Lee et al [68] performed the largest prospective observational study on the diagnostic value of presepsin in non-infectious organ failure, sepsis, and septic shock, in accordance with the latest Sepsis-3 definitions. They reported that presepsin has good accuracy in discriminating sepsis from non-infectious organ failure and had fair accuracy in discriminating septic shock from sepsis.…”
Section: Presepsin As a Diagnostic Markermentioning
confidence: 99%
“…A recently published single-center prospective observational study by Lee et al [68] reported prognostic value of presepsin among patients with non-infectious organ failure, sepsis, and septic shock (in accordance with Sepsis-3 definition) in ED. They identified the most useful presepsin cut-off value (821 pg/ml) for the prediction of 30-day mortality among patients with sepsis and septic shock.…”
Section: Presepsin As a Prognostic Markermentioning
confidence: 99%
“…Presepsin is one of the soluble forms of CD-14 and can be easily measured biochemically in serum, rises within 2 h after infection, and reaches its peak within 3 h; therefore, it is used as an early diagnostic and prognostic biomarker. [ 58 59 60 ] Presepsin was most frequently evaluated as a diagnostic biomarker in sepsis. The diagnostic sensitivity and specificity of presepsin in the diagnosis of sepsis were 0.94 (95% CI: 0.74–0.99) and 0.71 (95% CI: 0.35–0.92), respectively, and were superior to CRP and PCT in excluding sepsis.…”
Section: Presepsinmentioning
confidence: 99%
“…[ 58 ] Presepsin cutoff values for sepsis, septic shock, and 30-day mortality prediction were 582 pg/mL ( P < 0.001), 1285 pg/mL ( P < 0.001), and 821 pg/mL ( P = 0.005), respectively. [ 60 ] In a small case–control study of sepsis patients, presepsin levels were higher in the group that did not survive the early (<1 day) and follow-up measures (up to 7 days), in contrast to PCT. [ 61 ] However, in the meta-analysis, there was no significant difference in presepsin levels between the survivor and nonsurvivor groups (mean difference: 0.92 [95% CI: 0.62–1.22]) in the random-effects model (I 2 = 79%, P < 0.01).…”
Section: Presepsinmentioning
confidence: 99%